Estado nutricional em pacientes com neurofibromatose tipo 1 - Marcio Leandro Ribeiro de Souza (2014)
Introduction: Neurofibromatosis type 1 (NF1) is a genetic disease, autosomal dominant, which is mainly characterized by neurocutaneous changes, but may also have multisystemic involvement. Although the clinical manifestations of NF1 are well documented, the nutritional aspects are not well known. Consultation on MEDLINE, SCOPUS, Lilacs and SciELO not resulted in the meeting of studies that addressed eating habits, dietary pattern or nutrient intake in this population. Objective: To evaluate the nutritional status and food intake in patients with NF1. Methods: A sample of 60 NF1 patients (29 men and 31 women) aged 18 to 64 years were submitted to anthropometric, biochemical and dietary intake assessment. The following anthropometric parameters were measured: weight, height, circumferences (arm, head, waist, hip) and skinfolds (triceps, biceps, subscapular and suprailiac). From these measurements were calculated BMI, waist/hip ratio, arm muscle area (AMA) and arm fat area (AFA), and body composition. Also CBC tests, total cholesterol and fractions, triglycerides, total proteins and fractions, and fasting blood glucose were requested. Food intake were evaluated through one 24h recall and two food records, a total of three nonconsecutive days. The following diet constituents were investigated: energy, protein, lipid, cholesterol, carbohydrates, fiber, calcium, magnesium, manganese, phosphorus, iron, sodium, potassium, copper, zinc, thiamine, riboflavin, pyridoxine, niacin, vitamin C, vitamin D, vitamin A, and saturated, monounsaturated and polyunsaturated fatty acids, linoleic acid and linolenic acid. Results: The mean age of the study population was 34.48 ± 10.33 years old. Men showed greater weight, height, head circumference and fat-free mass than women with NF1. The short stature was found in 28.3% of the volunteers and the macrocephaly in 23.3%. Low weight was present in 10% of the sample, and 31.7% of patients had BMI25. The body fat percentage was considered high in 30% of volunteers. Waist circumference was greater in men with NF1. The AMA was higher in men with NF1 and 43.3 % of the total sample had low AMA. Men showed higher consumption of calories and daily energy expenditure than women. Forty-three patients (71.7%) present energy consumption below the estimated daily energy expenditure. Fifteen patients (25%) had excessive consumption of fats. For men with NF1, the inadequate nutrient intake was high in magnesium (87.28%), vitamin D (85.19%), calcium (73.02%) and pyridoxine (61.13%). Among women, the inadequate nutrient intake of vitamin D was high (90.37%), calcium (88.40%), magnesium (85.00%) and pyridoxine (83.44%). Forty-six patients (76.7%) showed consumption of saturated fatty acids above the recommended by WHO. All patients consumed excess sodium. Conclusions: Patients with NF1 in this study had a higher prevalence of underweight and short stature than Brazilian population. Also showed macrocephaly, high body fat percentage and reduced arm muscle area. In addition, there was inadequate consumption of nutrients like to vitamin D, magnesium, calcium and pyridoxine, insufficient consumption of fiber, vitamins A and C, and excessive consumption of saturated fatty acids and lipids. Changes in nutritional status and inadequate food consumption among patients with NF1 in this study reinforce the need for nutritional interventions in this population.